Serotonin and Inhibition in Limulus Lateral Eye - Adolph, A. R. (The Rockefeller University Press, 1972)
The response to light of one ommatidium is reduced or suppressed by simultaneous illumination of neighboring ommatidia. The mechanism of this lateral inhibition may be chemical synaptic transmission, based on the physiological findings of a number of investigators and on the following evidence. The fine structure of the neuropil of the lateral plexus exhibits numerous clear vesicles (ca. 400 A), dense-core vesicles (ca. 700–1400 A), Golgi regions, and other morphological features of neurochemical synapses. The indolealkylamine, serotonin (5-HT), even in nanomolar concentrations, has a potent inhibitory action. An initial, potent inhibitory dose of 5-HT produces a long lasting densensitization to subsequent doses. The desensitization affects lateral inhibition evoked by light stimulation of neighboring receptors, i.e. crossed-desensitization. Eye tissue extracts contain 5-HT and melatonin (MLT) at a level greater than 1 µg/g wet tissue and perhaps as high as 20–30 µg/g, as determined by two-dimensional thin-layer chromatography (TLC) and o-phthaldialdehyde fluorescence assay techniques. Subcellular fractionation on sucrose gradient indicates a peak in 5-HT and MLT content associated with an intermediate density fraction. 5-HT may be an inhibitory transmitter for lateral inhibition. One pathway for metabolism of 5-HT in the lateral eye may be via N-acetylserotonin and melatonin.